2017
DOI: 10.1080/14763141.2016.1265579
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a secondary cognitive task on landing mechanics and jump performance

Abstract: Anterior cruciate ligament (ACL) injuries commonly occur during jump-landing tasks when individuals' attention is simultaneously allocated to other objects and tasks. The purpose of the current study was to investigate the effect of allocation of attention imposed by a secondary cognitive task on landing mechanics and jump performance. Thirty-eight recreational athletes performed a jump-landing task in three conditions: no counting, counting backward by 1 s from a randomly given number, and counting backward b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 48 publications
3
37
0
Order By: Relevance
“…Lastly, more in-dividuals committed a cognitive erorr during the difficult cognitive task than the easy cognitive task. Previous studies have also demonstrated similar findings, supporting that there may be an increased risk of injury under dual-task conditions [5,[21][22][23][24][25]35].…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…Lastly, more in-dividuals committed a cognitive erorr during the difficult cognitive task than the easy cognitive task. Previous studies have also demonstrated similar findings, supporting that there may be an increased risk of injury under dual-task conditions [5,[21][22][23][24][25]35].…”
Section: Discussionsupporting
confidence: 66%
“…This current study also confirms prior reports that the addition of a cognitive dual-task to increase attentional demands [33,50] can result in increased injury risk due to neuromuscular control adaptations. Previous research has investigated dual-tasking during a drop vertical jump [22,23], cutting [21], and single-leg drop landing [24,25]. These previous investigations have shown that individuals have increased vertical ground reaction forces [22][23][24][25], decreased knee flexion angles [21][22][23], and increased knee abduction [21,22], all shown to be important lower extremity risk factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have demonstrated that ACL or LAS injuries often occur when athletes divert their attention to an opponent, ball, or some other target during jumping-landing tasks [12][13][14][15]. Almonroeder et al found that compared with male athletes, female athletes demonstrated greater landing force and peak knee abduction angles, as well as lower peak knee flexion angles, with additional cognitive demands while performing the drop vertical jump task [16].…”
Section: The Effect Of Divided Attention With Bounce Drop Jump On Dynmentioning
confidence: 99%